Twentieth Century Spanish American Poetry: European Replication and Experiments in the New World - Adhikari, Bam Dev (NPRC Journal of Multidisciplinary Research, 2025)
Twentieth century Spanish American poetry, while deeply rooted in its own cultural and historical contexts, reflects and adapts European avant-garde movements. During this period, major European literary experiments, including modernism, surrealism, and existentialism, significantly influenced the trajectory of Latin American poetic expression. Spanish American poets engaged with these European movements by incorporating new techniques such as free verse, and unconventional imagery, and rejecting traditional forms. Key figures like Vicente Huidobro, Jorge Luis Borges, Gabriela Mistral, Pablo Neruda, and Octavio Paz played pivotal roles in this shift, pushing the boundaries of language and representation. For example, Huidobro’s creation of "the poet as a god" in Creationism mirrored the surrealist focus on imagination and the unconscious. Likewise, Neruda’s Residence on Earth blended surrealist techniques with social and political commentary, reflecting European influences. Poets such as Octavio Paz, influenced by European existentialism and surrealism, crafted works that defined a unique Latin American identity and engaged with broader intellectual currents. While absorbing European innovations, these poets reinterpreted them in ways that reflected their national and regional realities, blending global movements with indigenous and local cultural elements. Thus, 20th-century Spanish American poetry represents both an echo and a creative transformation of European literary experimentation.